Innovation in Learning Methods for Improving Mastery of Arabic Vocabulary in Indonesian Junior High Schools | ibtikār ṭarīqat al-taʿallum fī zīyādah itqān al-mufradāt al-ʿarabiyyah bi-al-madrasa al-mutawassiṭah al-ḥukūmiyyah - Nurmalia Hidayah; Laily Fitriani; Abdul Aziz (Universitas Islam Negeri Palangka Raya, 2024)
There is still a perception that the singing method is only effective in small classes and with elementary school children. This study aims to apply the singing method as an innovative approach to learning Arabic vocabulary, in order to determine its impact on students' mastery of Arabic vocabulary in terms of pronunciation, fluency, and memorization. This research employs a qualitative approach with a descriptive data presentation method. Data collection techniques include observation and interviews regarding the application of the singing method. Data analysis techniques using the Miles and Huberman Model involve data reduction, data presentation, conclusion drawing, and verification. The results of this study conclude that teachers create positive resonances, stimuli, and affirmations to foster student comfort, confidence, and engagement in the classroom. Teachers then provide examples and repetitions of Arabic vocabulary songs they have created. Singing Arabic vocabulary, accompanied by music, initially engages even the least enthusiastic students. Students who initially lack confidence become more assured and dedicated, leading to improved fluency in pronouncing Arabic vocabulary.